Molecular investigation of Feline Panleukopenia in an endangered leopard (Panthera pardus) – a case report - S. M. Kolangath; S. V. Upadhye; V. M. Dhoot; M. D. Pawshe; B. K. Bhadane; A. P. Gawande; R. M. Kolangath (BMC Veterinary Research, 2023)
Abstract Background Feline Panleukopenia is an important disease of cats and has been reported worldwide. The disease is caused by a non-enveloped, single-stranded DNA virus; Feline Panleukopenia Virus (FPLV), belonging to the Parvoviridae family. The disease causes significant mortality in unvaccinated kittens. The disease has been well documented in companion animals. However, only a few reports have surfaced from the wild. Case presentation An orphan leopard cub was presented to Wildlife Rescue Centre, Nagpur, for further care; the leopard was kept under quarantine. On day 22 of the quarantine, the leopard showed inappetence, lethargy and depression and did not consume the offered carabeef (Day 0 of treatment). The leopard was examined clinically and was found to have a temperature of 102°F; blood was collected and analysed. On day one, the leopard exhibited bloody diarrhoea, inappetence, fever and depression. The leopard was rationally treated with fluids, antibiotics, multi-vitamins, haemostatics and haematinics. To gain qualitative insights into the epidemiological aspect of the disease, molecular investigation, including Polymerase Chain Reaction (PCR) and qPCR (Quantitative Polymerase Chain Reaction), were utilized to confirm the infection. The amplicon was sequenced and was found to be similar to sequences of FPLV reported domestic cats and other wild felids from India and abroad. Phylogenetic analysis was performed to understand the evolutionary relationship of the virus with previously reported sequences of FPLV. Sequences were submitted to National Center for Biotechnology Information (NCBI) and were allotted accession numbers. Conclusion The infection in endangered leopard cubs could be managed with prompt fluid therapy, antibiotics and support treatment, ensuring an uneventful recovery. Molecular investigation and sequencing efforts can provide valuable data on epidemiology and the evolutionary relationship of the virus with the circulating strains in the field. The study has implications in the preventive management of FPLV in captivity and the selection of strains for inclusion in vaccines meant for the wild felids.